2016
DOI: 10.9741/23736658.1020
|View full text |Cite
|
Sign up to set email alerts
|

Association between moral distress and job satisfaction of Japanese psychiatric nurses

Abstract: Moral distress of psychiatric nurses may affect their job satisfaction or quality of nursing care, thus examination of their moral distress is a significant issue for practice. The purpose of this study was to investigate the level of moral distress and job satisfaction, and association between moral distress and job satisfaction. One hundred and thirty nurses who worked in psychiatric wards in a hospital in Japan completed the Moral Distress Scale for psychiatric nurses (MDS-P) and the Job Satisfaction scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…All the nurses in this study worked in emergency wards. However, studies on nurses working in intensive care settings and clinical nurses documented a higher level of nurse autonomy (2,10,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…All the nurses in this study worked in emergency wards. However, studies on nurses working in intensive care settings and clinical nurses documented a higher level of nurse autonomy (2,10,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Mealer and Moss () note that nurses may often be disempowered in morally complex decision making with the power balance being typically shifted in favour of physicians, management or the overall hierarchically structured edifice of institutional power. Ongoing exposure to such disempowerment compounds moral distress and in the longer term may manifest in ‘psychological disequilibrium’, that is, emotional withdrawal, exhaustion and depersonalization, impaired respect for patient rights and care, increased job dissatisfaction and ultimately possible resignation from work (Ando & Kawano, ; Ando & Kawano, ; Mealer & Moss, ). Low staffing further compounds upon the climate in which there may be acquiescence to violations of patient rights, both of which serve to exacerbate moral distress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Low staffing further compounds upon the climate in which there may be acquiescence to violations of patient rights, both of which serve to exacerbate moral distress. This may create a downward spiral in which there is overall deterioration of nurses’ psychological well‐being and experience of working conditions (Ando & Kawano, ; Ando & Kawano, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…showed that 9 of job satisfaction subscales were relatively equal in their mean and SD, which the mean and SD of job satisfaction subscales ranged from 13.91 ± 1.77 to 14.83 ± 0.86. Table (2) explore the correlation between total job satisfaction score and total moral distress score as well as total sense of coherence score among studied nurses, as one can notice a highly statistically significance negative correlation was found between total job satisfaction score and total moral distress score. This means an increase in one variable of them is associated with a decrease in the other.…”
Section: Resultsmentioning
confidence: 96%